Curcumin and inflammatory bowel disease: potential and limits of innovative treatments. - Vecchi Brumatti, Liza; Marcuzzi, Annalisa; Tricarico, Paola Maura; Zanin, Valentina; Girardelli, Martina; Bianco, Anna Monica (Molecules, 2014)
Curcumin belongs to the family of natural compounds collectively called curcuminoids and it possesses remarkable beneficial anti-oxidant, anti-inflammatory, anti-cancer, and neuroprotective properties. Moreover it is commonly assumed that curcumin has also been suggested as a remedy for digestive diseases such as inflammatory bowel diseases (IBD), a chronic immune disorder affecting the gastrointestinal tract and that can be divided in two major subgroups: Crohn's disease (CD) and Ulcerative Colitis (UC), depending mainly on the intestine tract affected by the inflammatory events. The chronic and intermittent nature of IBD imposes, where applicable, long-term treatments conducted in most of the cases combining different types of drugs. In more severe cases and where there has been no good response to the drugs, a surgery therapy is carried out. Currently, IBD-pharmacological treatments are generally not curative and often present serious side effects; for this reason, being known the relationship between nutrition and IBD, it is worthy of interesting the study and the development of new dietary strategy. The curcumin principal mechanism is the suppression of IBD inflammatory compounds (NF-κB) modulating immune response. This review summarizes literature data of curcumin as anti-inflammatory and anti-oxidant in IBD, trying to understand the different effects in CD e UC.
Keywords: Animals; Anti-Inflammatory Agents, Non-Steroidal; Chemistry, Pharmaceutical; Clinical Trials as Topic; Curcumin; Humans; Inflammatory Bowel Diseases; Molecular Targeted Therapy; Nanotechnology; Treatment Outcome